Scanning tunneling microscopy/spectroscopy on Au nanoparticles assembled using lauryl amine (LAM) and octadecane thiol (ODT) - Datar, Suwarna; Chaudhary, Minakshi V.; Sastry, Murali; Dharmadhikari, C. V. (Applied Surface Science, 2007)
In this report, we demonstrate scanning tunneling microscopy and spectroscopy on thin filins of lauryl amine (LAM) and octadecane thiol (ODT) protected gold nanoparticles. We show that the zero current in the I-V curves (measure of Coulomb blockade (CB) of the nanoparticles) depends on the properties of the spacer molecule. In both the cases the gap voltage and the tunneling current at which the images are obtained are quite different which is further confirmed from the fitting performed based on the orthodox theory. The values for the capacitance and charging energy obtained from the fitting for ODT capped particles are comparable to the values obtained using spherical capacitor model. In contrast, values of these parameters were found to differ for LAM capped nanoparticles. While imaging, ODT capped nanoparticles were observed to drag along the scan direction leading to ordering of particles. Images of LAM capped gold nanoparticles show local ordering in self-assembly of particles although no evidence of large scale ordering in spatial Fourier transform was seen. These observations suggest that nanoparticles with larger CB would be intaged nonevasively in contrast to small CB systems for which tip induced effects will be dominant. In both the systems the current was found to rise faster than theoretical curves based on the orthodox theory suggesting that mechanism of charge transfer in this case may involve field emission rather than tunneling through a rectangular barrier. An attempt has been made to explain charge transfer based on Fowler-Nordheim (F-N) plots of the I-V curves. (c) 2006 Elsevier B.V All rights reserved.
Keywords: Nanostructures; scanning tunneling microscopy (STM)

Charge storage and electron transport properties of gold nanoparticles decorating a urethane-methacrylate comb polymer network - Patil, Sumati; Datar, Suwarna; Rekha, N.; Asha, S. K.; Dharmadhikari, C. V. (Nanoscale, 2013)
We propose enhanced charge storage capacity of nanoparticles based polymer films. A flat band voltage window varying from 5-7 V is obtained leading to a trapped charge density of the order of 10(13) cm(-2). These results vary for two distinct morphologies obtained due to decoration of a urethane-methacrylate comb polymer (UMCP) network by gold nanoparticles (AuNPs). Films have been further investigated for morphology, optical, charge storage, and electron transport properties using techniques like scanning electron microscopy (SEM), atomic force microscopy (AFM), absorption spectroscopy (UV-Vis), scanning tunneling microscopy/spectroscopy (STM/STS) and capacitance versus voltage (C-V) measurements. SEM and AFM confirm either the deposition of AuNPs inside the UMCP network or the formation of ring like structures depending on the deposition sequence. STS measurements performed on both films are compared with bare UMCP and AuNPs films. Current versus voltage (I-V) characteristics so obtained are discussed in the light of electron transport mechanisms in such materials.

Hysteretic DC electrowetting by field-induced nano-structurations on polystyrene films - Sawane, Yogesh B.; Datar, Suwarna; Ogale, Satishchandra B.; Banpurkar, Arun G. (Soft Matter, 2015)
Electrowetting (EW) offers executive wetting control of conductive liquids on several polymer surfaces. We report a peculiar electrowetting response for aqueous drops on a polystyrene (PS) dielectric surface in the presence of silicone oil. After the first direct current (DC) voltage cycle, the droplet failed to regain Young's angle, yielding contact angle hysteresis, which is close to a value found in ambient air. We conjecture that the hysteretic EW response appears from in situ surface modification using electric field induced water-ion contact with PS surface inducing nano-structuration by electro-hydrodynamic (EHD) instability. Atomic force microscopy confirms the formation of nano-structuration on the electrowetted surface. The effects of molecular weight, applied electric field, water conductivity and pH on nano-structuration are studied. Finally, the EW based nano-structuration on PS surface is used for the enhanced loading of aqueous dyes on hydrophobic surfaces.

Preparation of Ni3S2 and Ni3S2-Ni nanosheets via solution based processes - Busupalli, Balanagulu; Date, Kalyani S.; Datar, Suwarna; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2015)
An easy and convenient preparation of nanometer-thick sheets of Ni3S2 and Ni3S2–Ni from solution processed molecularly thin sheets of Ni-thiolates is described. Both the Ni3S2 and Ni3S2–Ni possessed sheet-like morphologies and displayed room temperature ferromagnetic characteristics. The ferromagnetic nature of these samples was also confirmed by MFM studies, and AFM/TEM investigations substantiated the sheet-like morphology of the samples.

Attempt to correlate surface physics and chemical properties : molecular beam and Kelvin probe investigations of Ce 1-x Zr x O 2 thin films - Kolekar, Sadhu K.; Dubey, Anjani; Date, Kalyani S.; Datar, Suwarna; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2016)
What is the correlation between physical properties of the surfaces (such as surface potential, electronic nature of the surface), and chemical and catalysis properties (such as chemisorption, sticking probability of surface)? An attempt has been made to explore any correlation that might exist between the physical and chemical properties of thin film surfaces. Kelvin probe microscopy (KPM) and the molecular beam (MB) methods were employed to carry out the surface potential, and oxygen adsorption and oxygen storage capacity (OSC) measurements on Ce1−xZrxO2 thin films. A sol–gel synthesis procedure and spin-coating deposition method have been applied to make continuous nanocrystalline Ce1−xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (35–50 nm); however, surface roughness and porosity inherently changes with CZ composition. MB studies of O2 adsorption on CZ reveal high OSC for Ce0.9Zr0.1O2, which also exhibits highly porous and significantly rough surface characteristics. The surface potential observed from KPM studies varied between 30 and 80 mV, with Ce-rich compositions exhibiting the highest surface potential. Surface potential shows large changes after reduction or oxidation of the CZ film demonstrating the influence of Ce3+/Ce4+ on surface potential, which is also a key to catalytic activity for ceria-based catalysts. The surface potential measured from KPM and the OSC measured from MB vary linearly and they depend on the Ce3+/Ce4+ ratio. More and detailed studies are suggested to arrive at a correlation between the physical and chemical properties of the surfaces.

Enhanced microwave absorption property of reduced graphene oxide (RGO)-strontium hexaferrite (SF)/poly (vinylidene) fluoride (PVDF) - Acharya, Sanghamitra; Gopinath, Chinnakonda S.; Alegaonkar, Prashant; Datar, Suwarna (Dimond and Related Materials, 2018)
Enormous growth in the use of electronic gadgets presents a challenge to develop efficient electromagnetic interference (EMI) shielding materials specifically using composites with properties such as light weight and high shielding due to absorption. In the present work we have synthesized a composite material with three components; Reduced Graphene Oxide (RGO) and Strontium Hexaferrite (SrFe12O19) (SF) bound together by polymer Poly (Vinylidene) Fluoride (PVDF). Composite RGO/SF (RGOSF) was prepared by facile one port chemical reduction method. Surface anchoring of similar to 500 nm of magnetic particles over the graphene sheet was confirmed by Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Crystal structure of SF particles was analyzed before and after composite formation with RGO. Effective crystallite size was estimated from both XRD and Raman Spectroscopy which showed similar trend moving from SF to RGOSF to RGOSFPVDF. Polymer composite films of RGOSFPVDF were prepared by hot pressing. Both real and imaginary part of magnetic and dielectric parameters were studied. It was observed that enhancement of interfacial polarization and anisotropic heat loss in PVDF matrix was generated by RGOSF which ultimately created more scattering center and helped in absorption of electromagnetic radiation. Critical film thickness of 3 mm was capable to shield up to 33 dB EM energy of which > 99.9% was due to absorption.

Investigation of disorder in mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon - Patil, Sumati; Kolekar, Sadhu; Kumar, Arvind; Alegaonkar, Prashant; Datar, Suwarna; Dharmadhikari, C. V. (Journal of Nanoscience and Nanotechnology, 2018)
Disorder in a mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon (GNC) lattice has been extensively studied for its electronic and field emission properties. Morphological investigations are performed using scanning electron microscopy (SEM) which depicts microstructures comprising of atomically flat terraces (c-planes) with an abundance of edges (ab planes which are orthogonal to c-planes). Scanning tunneling microscopy (STM) is used to observe the atomic structure of basal planes whereas field emission microscopy (FEM) is found to be suitable for resolving nanotopography of edges. STM images revealed the hexagonal and non-hexagonal atomic arrangements in addition to a variety of defect structures. Scanning tunneling spectroscopy is carried out to study the effect of this short-range disorder on the local density of states. Current versus voltage (I-V) characteristics have been recorded at different defect sites and are compared with respect to the extent of the defect. As sharp edges of GNC are expected to be excellent field emitters, because of low work function and high electric field, enhancement in current is observed particularly when applied electric field is along basal planes. Therefore, it is worthwhile to investigate field emission from these samples. The FEM images show a cluster of bright spots at low voltages which later transformed into an array resembling ledges of ab-planes with increasing voltage. Reproducible I-V curves yield linear Fowler-Nordheim plots supporting field emission as the dominant mechanism of electron emission. Turn on field for 10 mu A current is estimated to be similar to 3 V/mu m.
Keywords: Field emission microscopy; Graphene-Like Nanocarbon; Scanning tunneling microscopy; Scanning Tunneling Spectroscopy

Possible handle for broadening the catalysis regime towards low temperatures: proof of concept and mechanistic studies with CO oxidation on surface modified Pd-TiO2 - Mhamane, Nitin B. B.; Panchal, Suresh; Kolekar, Sadhu K. K.; Ranjan, Ravi; Salgaonkar, Kranti N. N.; Burange, Anand S. S.; Nalajala, Naresh; Datar, Suwarna; Gopinath, Chinnakonda S. S. (Physical Chemistry Chemical Physics, 2023)
The present work demonstrates the effect of temperature-dependent surface modification (SM) treatment and its influence in broadening the catalysis regime with Pd-TiO2 catalysts prepared by various methods. Due to SM induced changes, a shift in the onset of CO oxidation activity as well as broadening of the oxidation catalysis regime by 30 to 65 K to lower temperatures is observed compared to the temperature required for virgin counterparts. SM carried out at 523 K for Pd-Photo-TiO2 exhibits the lowest onset (10% CO2 production - T-10) and T-100 for CO oxidation at 360 and 392 K, respectively, while its virgin counterpart shows T-10 and T-100 at 393 and 433 K, respectively. The SMd Pd-TiO2 catalysts were investigated using X-ray photoelectron spectroscopy (XPS), ultra-violet photoelectron spectroscopy (UPS) and atomic force microscopy (AFM). It is observed that diffusion of atomic oxygen into Pd-subsurfaces leads to SM and changes the nature of the surface significantly. These changes are demonstrated by work function (& phi;), surface potential, catalytic activity, and correlation among them. UPS results demonstrate the maximum increase in & phi; by 0.5 eV for Pd-Photo-TiO2 after SM, compared to all other catalysts. XPS study shows a moderate to severe change in the oxidation states of Pd due to atomic oxygen diffusion into the subsurface layers of Pd. Kelvin probe force microscopy (KPFM) study also reveals corroborating evidence that the surface potential increases linearly with increasing temperature deployed for SM up to 523 K, followed by a marginal decrease at 573 K. The & phi; measured by KPFM and UPS shows a similar trend and correlates well with the changes in catalysis observed. Our results indicate that there is a strong correlation between surface physical and chemical properties, and & phi; changes could be considered as a global marker for chemical reactivity.

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG